Efficient Hydrolytic Hydrogen Evolution from Sodium Borohydride Catalyzed by Polymer Immobilized Ionic Liquid‐Stabilized Platinum Nanoparticles. Issue 4 (12th January 2022) - Doherty, Simon; Knight, Julian G.; Alharbi, Hussam Y.; Paterson, Reece; Wills, Corinne; Dixon, Casey; Šiller, Lidija; Chamberlain, Thomas W.; Griffiths, Anthony; Collins, Sean M.; Wu, Kejun; Simmons, Matthew D.; et al.
Abstract: Platinum nanoparticles stabilized by imidazolium‐based phosphine‐decorated Polymer Immobilized Ionic Liquids (PPh2 ‐PIIL) catalyze the hydrolytic evolution of hydrogen from sodium borohydride with remarkable efficiency, under mild conditions. The composition of the polymer influences efficiency with the catalyst based on a polyethylene glycol modified imidazolium monomer (PtNP@PPh2 ‐PEGPIILS) more active than its N‐alkylated counterpart (PtNP@PPh2 ‐ N ‐decylPIILS). The maximum initial TOF of 169 moleH2 .molcat −1 .min −1 obtained at 30 °C with a catalyst loading of 0.08 mol% is among the highest to be reported for the aqueous phase hydrolysis of sodium borohydride catalyzed by a PtNP‐based system. Kinetic studies revealed that the apparent activation energy (Ea ) of 23.9 kJ mol −1 for the hydrolysis of NaBH4 catalyzed by PtNP@PPh2 ‐PEGPIILS is significantly lower than that of 35.6 kJ mol −1 for PtNP@PPh2 ‐N‐decylPIILS. Primary kinetic isotope effects k H / k D of 1.8 and 2.1 obtained with PtNP@PPh2 ‐PEGPIILS and PtNP@PPh2 ‐ N ‐decylPIILS, respectively, for the hydrolysis with D2 O support a mechanism involving rate determining oxidative addition or σ‐bond metathesis of the O−H bond. Catalyst stability and reuse studies showed that PtNP@PPh2 ‐PEGPIILS retained 70 % of its activity across five runs; the gradual drop in conversion appears to be due to poisoning of the catalyst by the accumulated metaborate product as well as the increased viscosity of the reaction mixture. Abstract : Immobilized ionic liquid : Platinum nanoparticles stabilized by imidazolium‐based phosphine‐decorated Polymer Immobilized Ionic Liquids catalyze the hydrolytic evolution of hydrogen from sodium borohydride with a TOF of 169 moleH2 .molcat −1 .min −1 . Deuterium labelling studies for a tandem hydrogenation of 1, 1‐diphenylethene gave a mixture of all eight possible isotopologues consistent with facile reversible β‐hydride elimination‐reinsertion as well as rapid H/D exchange on Pd/C.